Analysis of autopsies conducted for deaths due to accidental trauma: a ten years record-based study - Ghadge, Mangesh Ramchandra; Samel, Dinesh Ramesh (International Journal of Research in Medical Sciences, 2017)
Background: Trauma is a largely preventable cause of death. Trauma can be avoided and death can be averted if timely medical services are made available. Hence it is important to know the causes of trauma, the factors associated with it and the types of fatal injuries associated with these causes. Methods: A ten years record based study of the autopsies conducted in the Forensic Medicine department of a rapidly growing metropolitan area was undertaken from the autopsy registers and post mortem records. Results: It was noted that the young age groups of 16 to 30 years and 31 to 40 years are most vulnerable. Major cause of trauma was road traffic accidents, followed by fall from height. Other causes are Rail accidents, domestic accidents, building collapse and industrial accidents. Head injuries and shock with hemorrhage are the major causes of death due to trauma. Conclusions: Overall, males and younger population forms a major proportion of trauma victims. Among female victims the major causes of trauma were domestic accidents and house collapse and among male victims road traffic accidents, fall from height and railway accidents were major causes.